An Opportunity Of Internet Marketing In Tourism Sphere - Shadiev Alisher Khudoynazarovich (Research Parks Publishers, 2021)
The article discusses an opportunity of internet marketing in tourism sphere. Frequent use of the Internet is becoming an integral part of the tourism industry. The use of the most powerful reservation systems for vehicles and means of accommodation on computers, cultural and recreational and excursion customer service, a large amount of information about the availability of certain places, routes, tours - all this becomes one of the main tasks that should be carried out by tourist organizations